ANALISIS PENERAPAN PEMBELAJARAN ONLINE PADA SISWA - Lina Novita; Hastri Nur Ismi (JURNAL MANAJEMEN PENDIDIKAN, 2021)
ANALYSIS TO THE APPLICATION OF STUDENTS ONLINE LEARNINGAnalysis to the Application of Students Online Learning . This study was a qualitative research with an analytic descriptive approach.This was a Thesis of the Elementary School Teacher of Education Study Program, Faculty of Teacher Training and Education, Pakuan University, Bogor, 2020. The purpose of this study was to analyze the application of online learning of grade III-A students at Cilubang 04 Elementary School, Bogor Regency which was carried out on the odd semester of the 2020/2021 Academic Year. The subjects of this study were all students of grade III-A. Data collection technique were conducted using observation, interviews and documentation. The results of this study indicated that students who followed online learning were facing several obstacles and difficulties. The obstacles and difficulties happened whenever the internet network connection was facing  problems for several times or difficult to access the internet that prevents students from participating the program. There was also the lack of understanding of students' parents about the online program and some parentsdid not have cellphones, that preventing. students to follow online learning activities. Student concentration was disturbed whenever they were getting bored with the ongoing  online learning and wanted to play with friends or watching television program that  broadcasted variety  interested entertainment program. And that was why it was hard to the students to understand the learning material. When students started to get bored and indolent to pay attention, teachers and parents should give motivation so the students enthusiasticallyfollowed the onlinet learning and more diligent. Whenever students got difficulty in understanding the subject matter provided, students directly asked the teacher or ask their parents to guide them during taking online learning. The learning or teaching method that  utilizing by teacher during conducting  online learning was by sending the subject matter through WhatsApp groupcompleted with instructional videos that attracted students' learning interest. Teacher also gave an assignments or questions through the WhatsApp group so the  students must work on time as specified by  the teachers.